THE INFLUENCE OF LIFESTYLE AND WORK ON PERCEPTION OF QUALITY AND ITS IMPLICATIONS ON PEARLY STORE PURCHASE DECISIONS - Citra Saffanah; Eka Elvira Br. Sinaga; Fitrianingsih; Imelda Mardayanti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of lifestyle and occupation on the perception of quality and its impact on consumer purchasing decisions at the Pearly Store in Tebing Tinggi City. In an era of increasingly tight retail competition, understanding the psychological and social factors of consumers is important for business actors. This study uses a quantitative approach with a survey method of 96 female consumer respondents who have shopped at the Pearly Store. The data analysis technique was carried out using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of the study indicate that lifestyle has a positive and significant effect on the perception of quality and purchasing decisions. Occupation has a significant effect on the perception of quality, but does not have a direct effect on purchasing decisions. Perception of quality is proven to have a significant effect on purchasing decisions, and acts as an intervening variable that mediates the relationship between occupation and lifestyle on purchasing decisions. These findings provide important implications for marketing strategies, especially in designing messages and products that are in accordance with the lifestyle and occupational background of the target market.